Transseksualiteit : nationaal colloqium 29 nov. 85 - Tacq, Anne-Mie; Bouman, Freek; Rubens, Robert (Brussel : Belgische Genderstichting, 1985)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure
Keywords: transgender